2016
DOI: 10.1159/000453142
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TGF-β Inducible microRNA-143 in Zebrafish Leads to Impairment of the Glomerular Filtration Barrier by Targeting Proteoglycans

Abstract: Background: TGF-β is known as an important stress factor of podocytes in glomerular diseases. Apart from activation of direct pro-apoptotic pathways we wanted to analyze micro-RNA (miRs) driven regulation of components involved in the integrity of the glomerular filtration barrier induced by TGF-β. Since miR-143-3p (miR-143) is described as a TGF-β inducible miR in other cell types, we examined this specific miR and its ability to induce glomerular pathology. Methods: We analyzed miR-143 expression in cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…These data are consistent with studies of TGF-binduced glomerulonephropathy in zebrafish. 37 Similarly, we detected a significant loss of ESL in AD-treated BALB/c mice.…”
Section: Discussionsupporting
confidence: 59%
“…These data are consistent with studies of TGF-binduced glomerulonephropathy in zebrafish. 37 Similarly, we detected a significant loss of ESL in AD-treated BALB/c mice.…”
Section: Discussionsupporting
confidence: 59%
“…We have confirmed the importance of this miR for the maintenance of a functional glomerular filtration barrier in the zebrafish model [16]. MiR-30 family members were also highly expressed in our cultured human podocytes.…”
Section: Discussionsupporting
confidence: 78%
“…We performed a Q-PCR based miR-screening (TaqMan® Array Human MicroRNA Card Set v3.0) in cultured human podocytes, human glomerular endothelial cells, human mesangial cells and human proximal tubular cells in unstimulated conditions and after stimulation of miR-143-3p for podocyte function and ultrastructure [16]. Examples for a glomerular endothelial cell and a mesangial cells-specific miRs are…”
Section: Mir-screening Setupmentioning
confidence: 99%
“…We demonstrated that miR-143-3p overexpression by injection of a specific miR-143-3p mimic in zebrafish egg stage leads to a significant reduction of vcan and sdc RNA isoforms in 120 days old zebrafish larvae. Moreover, miR-143-3p overexpression caused a nephrotic phenotype with generalized edema, loss of plasma proteins, podocyte effacement, glomerular endothelial cell swelling and loss of glomerular endothelial fenestration.Comparing the functional and ultra-structural glomerular changes of miR-143-3p overexpression to MO based knockdown of miR-143-3p target genes, vcan appeared to have the highest in vivo relevance because glomerular damage induced by miR-143-3p overexpression was comparable to that seen after vcan knockdown alone.We hypothesize that podocyte-derived miR-143-3p might function as a mediator for glomerular crosstalk between podocytes and glomerular endothelial cells and act in a paracrine as well as autocrine manner [18].Another miR that was cell-type specifically up regulated in cultured human podocytes after stimulation with TGF-beta was miR-378a-3p. miR-378a-3p was described to target nephronectin (NPNT) in osteoblasts [19].…”
mentioning
confidence: 97%
“…We hypothesize that podocyte-derived miR-143-3p might function as a mediator for glomerular crosstalk between podocytes and glomerular endothelial cells and act in a paracrine as well as autocrine manner [18].…”
mentioning
confidence: 99%